Changes in Serum Cystatin C Levels and the Associations With Cognitive Function in Alzheimer's Disease Patients - Chen, Xueping; Huang, Yan; Bao, Ting; Jia, Fu; Ou, Ruwei; Wei, Qianqian; Chen, Yongping; Liu, Jiao; Yang, Jing; Shang, Huifang (Frontiers in Aging Neuroscience, 2022)
Background and Objective Cystatin C is indicated to be involved in the pathogenesis of Alzheimer's disease (AD) and cognitive impairment. Our objective is to examine the serum Cystatin C levels, and to clarify the correlations between serum Cystatin C and cognitive performance in Chinese AD patients. Methods The serum Cystatin C concentrations in AD patients and age, sex, and body mass index (BMI) matched-healthy controls were measured. The cognitive functions of the AD patients were evaluated by using the Mini-mental State Examination (MMSE) and the Montreal Cognitive Assessment (MoCA). The severity of dementia was determined with clinical dementia rating (CDR). Results A total of 463 AD patients and 1,389 matched healthy subjects were included. AD patients had higher serum Cystatin C than healthy controls. Serum cystatin C levels were correlated with MoCA scores in AD patients. In an ordinal logistic regression model, AD patients with higher serum cystatin C levels had increased odds of severe cognitive dysfunction. Conclusion Our study suggested that AD patients had higher levels of serum cystatin C than age/sex/BMI-matched normal control subjects. Higher serum cystatin C may be associated with worse cognitive performance, but more studies are required to verify such association.